The structure of industry in London: 1775-1825 - Barnett, David Colin (1996)
This study sets out a quantitative overview of the economy of London during the period 1775 to 1825. A database has been constructed from the extant London Fire Office registers of 31,000 businesses trading either in the periods 1769-1777 or 1819- 1825, and in a few cases in both. Represented are over 1300 separate trades covering the entire spectrum of manufacturing, construction, wholesale and retail distribution, transport and the service sector. To complement this data, use has also been made of trade directories, bankruptcy files, trade card collections, Census data and contemporary literature on London trades, including career guides.